2023
DOI: 10.3390/w15081556
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Multiple Machine Learning Methods for Flood Routing in the Yangtze River

Abstract: Obtaining more accurate flood information downstream of a reservoir is crucial for guiding reservoir regulation and reducing the occurrence of flood disasters. In this paper, six popular ML models, including the support vector regression (SVR), Gaussian process regression (GPR), random forest regression (RFR), multilayer perceptron (MLP), long short-term memory (LSTM) and gated recurrent unit (GRU) models, were selected and compared for their effectiveness in flood routing of two complicated reaches located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…The idea of SVR is that an entire sample set can be characterized by a small number of support vectors [30]. In SVR, a kernel function is used to create a linearly divisible space by converting the sample space, and then predictive analysis on the new samples is performed using the hyperplane with the largest margin and support vectors [14]. The learning ability of a SVR model is highly affected by the selected kernel function.…”
Section: Single Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…The idea of SVR is that an entire sample set can be characterized by a small number of support vectors [30]. In SVR, a kernel function is used to create a linearly divisible space by converting the sample space, and then predictive analysis on the new samples is performed using the hyperplane with the largest margin and support vectors [14]. The learning ability of a SVR model is highly affected by the selected kernel function.…”
Section: Single Applicationmentioning
confidence: 99%
“…In this study, the dynamics of the studied floods were captured by applying the SVM to observed data, and the model showed good performance for flood routing modeling. Katipoglu and Sarigol [27] compared the performance of various ML models, including SVM, for flood routing prediction in Eskisehir, Sivas, and Ankara, and Zhou and Kang [14] used a linear kernel in a SVR for flood routing in the Yangtze River.…”
Section: Single Applicationmentioning
confidence: 99%
See 3 more Smart Citations